Organizacijska kultura in klima v storitvenem podjetju - Škerget, Tina (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
In today’s time, especially in times of recession, companies are fighting for the best possible position on the market and the biggest market share, and compete with each other in the fields of innovation, flexibility, resourcefulness - in diversity. All this struggle is the consequence of each company’s desire to achieve a competitive advantage over rivals, create as favourable market position as possible and a reputation, and thereby to maximize the profit. All this is affected by various factors, but the biggest effect can be attributed to the employees. They are the heart of every society. Hence, the key to success are good mutual relations and satisfied employee - or more precisely a good organizational culture and climate in the company. In the research part of the paper we conducted in a services company a survey about organizational climate and culture and employee satisfaction. The findings suggest that organizational climate and culture in the company are relatively good and even above the Slovenian average. The results showed that the best assessed categories are internal relations, professional competence and learning attitude, attitude towards quality, innovation and initiative, motivation and enthusiasm. The worst-evaluated categories are organizational structure, internal communication and informing, knowledge of the company’s mission and objectives, remuneration and career development.